Orikkal tur̲annāl aṭayātta vātilukaḷ - Santōṣ Māniccēri (Insight Publica, 2020)
Critical study on Malayalam poetry; previously posted at facebook.
Enthält Literaturverzeichnis
Keywords: Malayalam poetry; 20th century; History and criticism.